2021
DOI: 10.7759/cureus.16705
|View full text |Cite
|
Sign up to set email alerts
|

Monopolar Transurethral Resection of Prostate for Benign Prostatic Hyperplasia in Patients With and Without Preoperative Urinary Catheterization: A Prospective Comparative Study

Abstract: BackgroundA significant proportion of patients undergo surgery for benign prostatic hyperplasia following acute urinary retention. Studies have reported conflicting results of improvement following transurethral surgery in these patients. ObjectiveTo compare perioperative complications and postoperative voiding parameters in patients undergoing monopolar transurethral resection of prostate with and without preoperative Foley catheterization. MethodsA prospective non-randomized study was conducted in patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This could be explained as an outcome of upper tract versus lower tract colonization. Similar outcomes were reported by Chen and Adhikari in patients undergoing TURP, where those with Acute Urinary Retention (AUR) on Foley did not have a higher incidence rate of UTI 25,26 …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This could be explained as an outcome of upper tract versus lower tract colonization. Similar outcomes were reported by Chen and Adhikari in patients undergoing TURP, where those with Acute Urinary Retention (AUR) on Foley did not have a higher incidence rate of UTI 25,26 …”
Section: Discussionsupporting
confidence: 70%
“…Similar outcomes were reported by Chen and Adhikari in patients undergoing TURP, where those with Acute Urinary Retention (AUR) on Foley did not have a higher incidence rate of UTI. 25,26 Multiple studies demonstrated that diabetes is a well-known risk factor for post-operative urinary infection in endourological surgeries. [27][28][29] In our study, however, diabetes did not seem to confer a higher risk of bacteriuria.…”
Section: Urologists In the Developing Countries Continue To Usementioning
confidence: 99%
“…This test is conducted when the risk of postoperative urinary retention (POUR) is low. After a transurethral resection of the prostate, the test is usually conducted when hematuria is no longer present [2,3]. After radical prostatectomy, there is a typical delay of 5 to 12 days to obtain a secure bladder neck anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…The primary risk factor for failing multiple tests is overdistention or the bladder prior to surgery, denervation or urethral injury during childbirth. Secondary risk factors include advanced age, obesity and smoking [3,4,6].…”
Section: Introductionmentioning
confidence: 99%